Introduction to 3D game programming with DirectX 11 - Luna, Frank D., ....- (Dulles (Va.) : Mercury Learning and Information, 2012)
This updated bestseller provides an introduction to programming interactive computer graphics, with an emphasis on game development using DirectX 11. The book is divided into three main parts: basic mathematical tools, fundamental tasks in Direct3D, and techniques and special effects. It includes new Direct3D 11 features such as hardware tessellation, the compute shader, dynamic shader linkage and covers advanced rendering techniques such as screen-space ambient occlusion, level-of-detail handling, cascading shadow maps, volume rendering, and character animation. Includes a companion CD-ROM with code and figures.
Keywords: Computer games -- Programming; Spelprogrammering